Peran Karang Taruna dalam Membentuk Generasi Digital Native Islami di Kelurahan Banaran, Kecamatan Kertosono, Kabupaten Nganjuk melalui Pendekatan Berbasis Nilai-Nilai Keislaman - Muhammad Maulana Malik Abdul Aziz (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study discusses the role of the Banaran Village Youth Organization, Kertosono District, Nganjuk Regency in forming an Islamic-based native digital generation. The purpose of the research is to describe the role, strategy, and analyze the supporting factors and obstacles of Karang Taruna in forming a digitally literate Islamic generation. The data was analyzed using the source triangulation technique. The results of the study show that Karang Taruna plays a role as a forum for learning and self-development, through routine religious programs, digital literacy training, and the development of technological creativity based on Islamic values.